Intellectuals, hegemony and education in the Prison Notebooks. A reading from the new philological and hermeneutical studies on Antonio Gramsci (Praxis Educativa, 2022)
The article investigates the educational question in the Prison Notebooks from the binomial intellectuals and hegemony. A reference in Latin American critical educational theory, Antonio Gramsci encourages educational studies in the region. However, this assiduous evocation is not often accompanied by a subtle knowledge of the theoretical and historical plot of prison concepts. Hiatus that has become more eloquent in recent decades, when his work is increasingly investigated in a philological key and renewed keys of interpretation emerge.In order to explore the pedagogical topic in Gramsci, the article links the hegemony / intellectuals binomial with the notions of hegemony crisis, passive revolution and permanent revolution. In this way, proposes to address the question of intellectuals and education in the Prison Notebooks through the following series: on the one hand, bourgeois hegemony - passive revolution - passive pedagogy; on the other, proletarian hegemony - permanent revolution - active pedagogy.
Keywords: Antonio Gramsci; Prison Notebooks; education; intellectuals; hegemony